2016
DOI: 10.17645/pag.v4i1.471
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Explosion of EU News on Voter Choice in the 2014 EU Elections

Abstract: The European elections in 2014 were the first to be held after a long period in which EU-related news was prominent in the media. They were held after years of daily news about the euro crisis and after months of news about the popular uprising in the Ukraine against president Yanukovych, who had refused to sign the association agreement with the EU. This could have invited political parties to overcome the usual problem of low salience of EU issues by strongly profiling themselves on EU issues. Turnout at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Media content is not fully governed by prior media choice either. Unexpected new issues with surprising or ambiguous issue positions of parties may come to dominate the news, also in self-selected media, like the EU-Ukraine relationship in the run-up to the European elections of 2014 (Kleinnijenhuis & van Atteveldt, 2016), on which this study concentrates. While the self-selection of media by partisans might be guided by predispositions that derive from traditional cleavage dimensions like the dominant socio-economic left-right dimension, so-called wedge issues do not align with these traditional cleavages (Kriesi et al, 2006; van de Wardt, De Vries, & Hobolt, 2014).…”
Section: Compatibility Of the Fmp And Hmementioning
confidence: 99%
“…Media content is not fully governed by prior media choice either. Unexpected new issues with surprising or ambiguous issue positions of parties may come to dominate the news, also in self-selected media, like the EU-Ukraine relationship in the run-up to the European elections of 2014 (Kleinnijenhuis & van Atteveldt, 2016), on which this study concentrates. While the self-selection of media by partisans might be guided by predispositions that derive from traditional cleavage dimensions like the dominant socio-economic left-right dimension, so-called wedge issues do not align with these traditional cleavages (Kriesi et al, 2006; van de Wardt, De Vries, & Hobolt, 2014).…”
Section: Compatibility Of the Fmp And Hmementioning
confidence: 99%
“…From then onwards they were also visible in traditional, online and social media across several European countries (Gattermann, 2020). Further-more, Kleinnijenhuis and van Atteveldt (2016) demonstrated that EU news had already been prominent for several months prior to the 2014 EP elections, which is why our time period can be considered part of the campaigns.…”
Section: Methodsmentioning
confidence: 82%
“…When news stories focus on the Euro crisis, for instance, the visibility of candidates in EU news is not an indicator of support for European integration but often generates opposition or enhances Eurosceptic attitudes (Kleinnijenhuis & van Atteveldt, 2016). In the same vein, the news coverage of the EU crisis is found to give selective salience to Eurosceptic actors and lower visibility to EU actors and their policies (Boomgaarden et al, 2013, pp.…”
Section: Taking Media Logics Seriouslymentioning
confidence: 99%
“…Rightwing Eurosceptic party groupings altogether gained a significant minority of the seatsthe European Conservatives and Reformists (ECR), formed by former British Prime Minister David Cameron in 2009, won 70 seats (9.32 per cent), and two newly formed groups -Europe of Freedom and Direct Democracy (EFDD) and Europe of Nations and Freedom won 48 (6.39 per cent) and 39 (5.2 per cent) respectively. Even though the salience of the EU in the news increased between the 2009 and 2014 EP elections, (Kleinnijenhuis & van Atteveldt, 2016), this politicisation of the EU in public debates is often driven by more fundamental conflicts about EU constitutional issues, the EU's external relations or crisis (de Wilde et al, 2013;Hutter et al, 2016). The intended politicisation of the EP elections has therefore not necessarily happened along the left/right spectrum but along identitarian lines (Grande and Kriesi 2015, Hooghe and Marks 2009).…”
Section: Introductionmentioning
confidence: 99%